2003
DOI: 10.1080/13651820310015293
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic cholecystectomy: incidents and complications. A retrospective analysis of 9542 consecutive laparoscopic operations

Abstract: BackgroundEven though laparoscopic cholecystectomy (LC) has become the customary method for treating gallstones, some incidents and complications appear rather more frequently than with the open technique. Several aspects of these complications and their treatment possibilities are analysed. Materials and methodsOver the last 9 years 9542 LCs have been performed at this centre, of which 13.9% were carried out for acute cholecystitis, 38.4% in obese patients and 7.6% in patients aged >65 years. ResultsThe main … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(43 citation statements)
references
References 15 publications
0
40
0
3
Order By: Relevance
“…The estimated rate of gallbladder perforation is 10-30%. Duca et al [8] reported that the incidence of iatrogenic perforation of the gallbladder was 1,517 (15.9%) out of 9,542 patients who underwent laparoscopic cholecystectomy. In our study, we report 39 (5.27%) iatrogenic perforations of the gallbladder.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The estimated rate of gallbladder perforation is 10-30%. Duca et al [8] reported that the incidence of iatrogenic perforation of the gallbladder was 1,517 (15.9%) out of 9,542 patients who underwent laparoscopic cholecystectomy. In our study, we report 39 (5.27%) iatrogenic perforations of the gallbladder.…”
Section: Discussionmentioning
confidence: 99%
“…The most serious complications are associated with high mortality rate: injury of common bile duct with an incidence of 0.1-0.6% [5, 6], injuries of large blood vessels 0.04-1.22% depending on the study [7]. The most common complication is iatrogenic perforation of the gallbladder with spilt gallstones with an incidence of 10-30% [8]. Injuries during the laparoscopic cholecystectomy can be prevented by precise operative technique, clear visualisation of anatomical landmarks, and careful dissection of tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Pericholecystitis makes laparoscopy challenging, changes the local anatomy, and increases the difficulty of identifying the Calot's triangle and common bile duct. Pericholecystitis can also predispose the patient to hemorrhage more easily from the gallbladder bed or cystic artery, and it causes an increased risk of gallbladder perforation and, thus, spillage of gallstones into the peritoneal cavity during dissection of the gallbladder 17. Thus, conversion rates in cases with AC were reported in the literature to reach up to 27.7% 18.…”
Section: Discussionmentioning
confidence: 99%
“…This is followed by postoperative haemorrhage and sub-hepatic abscess formation, which occur in less than 0.1% of patients. 9 Conversion to an open procedure may be required in up to 2% of cases, usually because of post-inflammatory changes that impede laparoscopic identification of anatomy. Bowel injury is a potential complication of any laparoscopic procedure that can result from electrocautery or port-site trochar insertion.…”
Section: Discussionmentioning
confidence: 99%